N6-Methyladenosine-Modified circRNA in the Bovine Mammary Epithelial Cells Injured by Staphylococcus aureus and Escherichia coli - Xu, Haojun; Lin, Changjie; Li, Ting; Zhu, Yifan; Yang, Jinghan; Chen, Sijie; Chen, Jianguo; Chen, Xi; Chen, Yingyu; Guo, Aizhen; Hu, Changmin (Frontiers in Immunology, 2022)
Mastitis is a common disease that hinders the development of dairy industry and animal husbandry. It leads to the abuse of antibiotics, the emergence of super drug-resistant bacteria, and poses a great threat to human food health and safety. Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) are the most common pathogens of mastitis in dairy cows and usually cause subclinical or clinical mastitis. CircRNAs and N6-methyladenosine (m6A) play important roles in immunological diseases. However, the mechanisms by which m6A modifies circRNA in bovine mammary epithelial cells remain poorly understood. The aim of our study was to investigate m6A-modified circRNAs in bovine mammary epithelial cells (MAC-T cells) injured by S. aureus and E. coli. The profile of m6A-modified circRNA showed a total of 1599 m6A peaks within 1035 circRNAs in the control group, 35 peaks within 32 circRNAs in the S. aureus group, and 1016 peaks within 728 circRNAs in the E. coli group. Compared with the control group, 67 peaks within 63 circRNAs were significantly different in the S. aureus group, and 192 peaks within 137 circRNAs were significantly different in the E. coli group. Furthermore, we found the source genes of these differentially m6A-modified circRNAs in the S. aureus and E. coli groups with similar functions according to GO and KEGG analyses, which were mainly associated with cells injury, such as inflammation, apoptosis, and autophagy. CircRNA-miRNA-mRNA interaction networks predicted the potential circRNA regulation mechanism in S. aureus- and E. coli-induced cell injury. We found that the mRNAs in the networks, such as BCL2, MIF and TNFAIP8L2, greatly participated in the MAPK, WNT, and inflammation pathways. This is the first report on m6A-modified circRNA regulation of cells under S. aureus and E. coli treatment, and sheds new light on potential mechanisms and targets from the perspective of epigenetic modification in mastitis and other inflammatory diseases.